ANALISA TERHALANGNYA PANDANGAN TOWER CONTROLLER AKIBAT VERTICAL SUPPORT (PILAR) DI CABIN TOWER PERUM LPPNPI CABANG MEDAN - Pramudya, Reynaldi; Rahayu Surtiningtyas, Sri; Praptiningsih, Nunuk; Novianti, Lizti (Jurnal Penelitian, 2024)
Tower controllers are air traffic control officers responsible for managing air traffic around airports to ensure safety, security, and efficiency in aircraft movements. They work in airport control towers, which serve as the central hub for air traffic control in the vicinity of the airport. Control towers are typically located near the runways and provide good visibility for monitoring aircraft movements on the ground and in the air. Within the control tower, the equipment and comfort of the air traffic controllers are important considerations. This research focuses on the control tower of Perum LPPNPI branch in Medan, where it has been found that wide-diameter pillars obstruct the view of the tower controllers. The aim of this study is to analyze the pillars as an obstruction and provide recommendations to Perum LPPNPI branch in Medan on how to address this issue. The research methodology employed is qualitative. The research findings conclude that the pillars indeed pose an obstruction, and the author suggests that Perum LPPNPI branch in Medan relocate the control desk. Tower controller adalah petugas yang mengatur lalu lintas udara di sekitar bandar udara dengan tujuan memastikan keselamatan, keamanan, dan efisiensi pergerakan pesawat. Mereka bekerja di menara kontrol yang terletak di bandar udara dan berfungsi sebagai pusat pengendalian lalu lintas udara. Menara kontrol biasanya terletak dekat landasan pacu dan memberikan visibilitas yang baik untuk memantau pergerakan pesawat di darat dan udara. Di dalam menara kontrol, peralatan dan kenyamanan pemandu lalu lintas perlu diperhatikan. Penelitian ini berfokus pada menara kontrol Perum LPPNPI cabang Medan, dimana ditemukan di dalam menara kontrol bahwa pilar yang berdiameter lebar mengganggu pandangan para tower controller. Penelitian ini bertujuan untuk menganalisis pilar tersebut sebagai gangguan dan memberikan saran kepada Perum LPPNPI cabang Medan tentang menangani masalah tersebut. Metode penelitian yang digunakan adalah kualitatif. Hasil penelitian tersebut adalah disimpulkan bahwa pilar tersebut menjadi gangguan, dan penulis memberikan saran agar pihak Perum LPPNPI cabang Medan memindahkan control desk.